Perspectives on emotional memory images and the persistence of pain - Hudson, Matt; Johnson, Mark I. (Frontiers in Pain Research, 2023)
Multiple influences prevent recovery from pain. Our viewpoint is that non-conscious emotional memory images (EMIs) triggers outdated stress responses contributing to the intractability of pain. In this perspectives article we explore the concept that EMIs contribute to the persistence of pain. We contend that psychophysiological “stress” responses, resulting from first-time, novel and unprecedented pernicious or adverse events form EMIs within very short time frames (split-second learning). Subsequently, these EMIs are re-triggered in daily living, “re-playing” stress responses. We postulate that EMIs continually “raise the alarm” to socio-ecological stimuli by re-triggering the HPA-axis and amplifying neural input associated with threat, fear, anxiety, and pain, creating a debilitating state of psychophysiological dis-ease. We position the EMI within a philosophical debate on the nature and locus of memory and explain how the EMI, irrespective of whether it is a “thing” or a metaphor, can create a basis of understanding for the client to grasp. We describe a therapeutic approach (Split-Second Unlearning) to “clear” EMIs and the “stickiness” of pain and help people embark on a healing journey. This involves surveillance of clients for micro-expression(s) signifying an in-the-moment stress response, representative of the presence of an EMI, and encouraging the client to become a curious observer within/of their own experience. This helps the client detach their EMI from its stress response. We contend that this occurs rapidly without the need to get bogged down in a whole-life narrative. We advocate further exploration of our EMI model of dis-ease in the context of intractable pain.